2019
DOI: 10.2118/195597-pa
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of High-Temperature Raw-Seawater-Based Fracturing Fluids

Abstract: Summary Typically, water-based fracturing treatments consume a large volume of fresh water. Providing consistent freshwater sources is difficult and sometimes not feasible, especially in remote areas and offshore operations. Therefore, several seawater-based fracturing fluids have been developed in an effort to preserve freshwater resources. However, none of these fluids minimizes fracture-face skin and proppant-conductivity impairment, which can be critical for unconventional well treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Also, diammonium EDTA and sodium gluconate formed complexes, with the borate ion preventing the cross-linking from taking place. Almubarak et al 160 also investigated the possibility of using seawater for hydraulic fracturing, instead of fresh water. The study suggested using polyphosphates and organophosphorus as scale inhibitors, where they act as chelating agents.…”
Section: Chelating Agents As Hydraulic Fracturingmentioning
confidence: 99%
“…Also, diammonium EDTA and sodium gluconate formed complexes, with the borate ion preventing the cross-linking from taking place. Almubarak et al 160 also investigated the possibility of using seawater for hydraulic fracturing, instead of fresh water. The study suggested using polyphosphates and organophosphorus as scale inhibitors, where they act as chelating agents.…”
Section: Chelating Agents As Hydraulic Fracturingmentioning
confidence: 99%
“…Another test with sodium sulfate as the brine was conducted to test the effect of sulfate ions on the foam decay. Sulfate ions are commonly available in seawater brines [29]. The presence of sulfate ions was detrimental to foam stability.…”
Section: Hpvc Foam Testsmentioning
confidence: 99%
“…HEDTA and EDTA were used as additives for produced and seawater fracturing fluids. Compatible chelating/water solutions were achieved at a salinity level of 101 000 ppm, and reasonable fluid viscosity was generated at 180 °F and 100 s –1 shear rate. …”
Section: Introductionmentioning
confidence: 99%